Budaya Kerja dalam Peningkatan Pelayanan Publik pada Kantor Pengadilan Negeri Sampit Kelas IB: Work Culture in Improving Public Services at the Class IB Sampit District Court Office - Hidayanti, Rakhmah; Saipul, Saipul; Junaidi, Junaidi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This research aims to analyze the need for a new work culture in improving the capacity and capability of Civil Servants (ASN) at the Class IB District Court of Sampit. The research method used in this study was in-depth interviews and documentary studies. Research respondents consisted of officials and staff at the court. The results showed that there is a significant need for the adoption of a new work culture that is more open, inclusive, and oriented towards public service. A work culture that supports collaboration, innovation, and continuous learning was identified as a key factor in enhancing the capacity and capability of ASN. The implications of this research suggest the need for changes in management policies and practices in the court to create a work environment that supports the professional growth and development of ASN.